Efektifitas Mindfulness Berbasis Fase Menstruasi Terhadap Kecerdasan Emosional Remaja Perempuan - Satiti, Ika Arum Dewi; Ekasari, Rizqiana Dita (Jurnal Ners, 2025)
Adolescence is a critical period of emotional development, particularly among adolescent girls who experience hormonal fluctuations during the menstrual cycle. These hormonal changes may trigger emotional instability, thus requiring effective emotion regulation strategies. Menstrual phase based mindfulness is considered a contextual approach to enhance adolescents’ emotional intelligence. This study aimed to determine the effectiveness of menstrual phase based mindfulness interventions on the emotional intelligence of adolescent girls. A quantitative method with a quasi-experimental pre–posttest with control group design was conducted among 60 students at Muhammadiyah 1 Vocational High School in Malang. The research instrument used was the Trait Emotional Intelligence Questionnaire – Adolescent Short Form (TEIQue-ASF). The intervention group received mindfulness practices tailored to the menstrual phase, including body scan during menstruation, grounding during the follicular phase, and journaling during the luteal phase, while the control group was only given aromatherapy. Data were analyzed using the paired t-test. The results showed that emotional intelligence scores significantly increased in the intervention group compared to the control group (p < 0.05). The greatest improvement occurred in the follicular phase (103.6 ± 7.8 to 116.3 ± 6.9), followed by the luteal phase (99.8 ± 8.6 to 110.7 ± 7.8), ovulation phase (104.1 ± 7.5 to 114.2 ± 7.1), and menstruation phase (102.4 ± 8.2 to 111.6 ± 7.5). These findings demonstrate that menstrual phase–based mindfulness effectively improves emotional intelligence in adolescent girls, particularly during the follicular phase, and has the potential to be developed as a promotive-preventive program in schools to support adolescent mental health.